KOMUNIKASI PUBLIK DAN SISTEM SOSIAL MASYARAKAT DALAM MENGHADAPI PANDEMI COVID-19 - Yosieana Duli Deslima (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2020)
Indonesia is currently facing a covid-19 pandemic. The situation is increasingly difficult,positive cases of covid-19 are increasing. Various efforts were made to prevent covid-19 transmission. Each region reaps the pros and cons and have different problems and require different ways of dealing with it. Each local leadershas a different strategy and socialization so that what is conveyed can be heard and done by the community. Submission of communication messages built by the Government of the City of Bandar Lampung through Diskominfotik to control the social system of the community seems to be still weak because there are still many hoaxes that are trusted by the community that cause excessive panic. This is where the role of public communication is needed, to provide information to the community, calm the community, to unite together against covid-19. In addition, a very important thing to do is to strengthen public communication on the role of local governments in informing and providing education to the local community. So that the social system remains balanced and does not experience inequality in the face of the current covid-19 pandemic. United against covid-19.